“It’s as Important as Biology”: Politics and Nursing, a Discussion with Nurse and Mayor Gracia Kasoki Katahwa - Natalie Stake-Doucet and Sophia Cérat (Nursing Leadership, 2022)
Based around an interview with nurse-turned-mayor Gracia Kasoki Katahwa, the authors present a teaching case study of nurses' political agency. The experience of Mayor Katahwa within nursing and in politics allows the authors to bridge systemic issues with lived experience. The article offers unique insights into political agency and how it can be developed in nurses.
Keywords: nurses; case study; political agency; Mayor Katahwa; systemic issues